Progressive Legal Approach to Modern Community Law Enforcement in Indonesia - Syinta Amelia (Pancasila and Law Review, 2023)
Law is the rule of norms and sanctions made to regulate human behavior, maintain order and justice, and prevent chaos. Law functions to guarantee the existence of legal law in society. Influence does not mean identical. The Indonesian legal system is not the same as the Anglo-American. Law in Indonesia refers to the development of law in Indonesia. The Indonesian legal system is a system itself. A system built from the process of discovery, development, adaptation and even compromise of several existing systems or it can be said the Pancasila legal system. Usually, laws change due to changing elements in life. However, this does not mean that the law is always in a dependent position. Social changes caused by technological developments lead to modern life because modernization has penetrated traditional rural communities due to these technological advances. Law enforcement in Indonesia through social analysis and progressive law is categorized as a new paradigm in law enforcement in Indonesia that is relevant to progressive law as the fulfillment of justice. This study uses library research methods and data management techniques. However, because the scope of this research is only in legal disciplines, this research was conducted by examining literature, laws and other written materials or known as normative legal research which is descriptive in nature and researched with legal socio-legal. The research results show that the assumption used is to make the law a social phenomenon. Social analysis is needed to examine various law enforcement problems because the law is part of social phenomena. The use of progressive law is a legal thought introduced and developed by Satjipto Rahardjo by viewing law as a social phenomenon.